PENGARUH FINANCIAL CLASSIFICATION, FINANCIAL INDICATORS, DAN CORPORATE PERFORMANCE TERHADAP MANAJEMEN LABA - Orlin Cicilia (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
The purpose of this study is to know the analysis of the effect of financial classification, financial indicators, and corporate performance on earning management through corporate governance as intervening variable. Financial indicators of this study are measured by liquidity, profitability, and leverage. Sampling method used is purposive sampling method (a method using special criterias). The sample in this study is 54 manufactur companies listed on the Indonesia Stock Exchange in 2011-2014. This research uses IBM SPSS 21.0 and variety of journals and references relating to the topic of this research contained in the library as well as other information from legal website on the internet. The result of this study shows that financial classification, financial indicators, and, corporate performance don’t have significant influence to earning management indirectly through corporate governance as intervening variable. The direct and significant influence only happen to profitability on earning management